Load Frequency Control (LFC) Strategy for an Isolated Microgrid Integrated with Electric Vehicles - Visa, S. B.; Chun, A.D.; Charles, I. H.; Hassan, Rufai; Gasin, S. C. (Darul Yasin Al Sys, 2025)
The growing demand for efficient and sustainable energy solutions has driven the widespread adoption of Distributed Energy Resources (DERs) and microgrids. However, the intermittent nature of DERs and the low inertia of isolated microgrids present significant challenges for Load Frequency Control (LFC). Primary frequency control alone often fails to maintain system frequency within acceptable limits. To address this issue, this research proposes an LFC strategy for a hybrid standalone microgrid (SMG) leveraging electric vehicles (EVs). The approach incorporates a Proportional-Integral-Derivative (PID) controller in the SMG design model. The objective function is formulated using the Integral of Time-Weighted Absolute Error (ITAE), and the Particle Swarm Optimization (PSO) algorithm is employed to optimize the PID gain parameters. Furthermore, Flywheel Energy Storage System (FESS) and Battery Energy Storage System (BESS) components are integrated with the PID controller's output to enhance LFC performance. The system capitalizes on the high-energy density and bidirectional charging/discharging capabilities of EVs to effectively regulate frequency variations. The effectiveness of the proposed method is validated through three simulation scenarios. In Scenario 1, the proposed technique achieves a 61.82% improvement in frequency deviation and a 40% reduction in settling time. Scenario 2 shows further enhancement, with improvements of 78.26% in frequency deviation and 61.54% in settling time. The simulation results consistently demonstrate that the proposed technique outperforms existing methods across all scenarios in terms of frequency deviation and settling time improvements.